Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Squaraine-linked metalloporphyrin two-dimensional polymer photocatalyst for hydrogen and oxygen evolution reactions - Ranjeesh, K. C.; George, L.; Wakchaure, V. C.; Goudappagouda; Devi, R. N.; Babu, S. S. (Chemical Communications, 2019)
Efficient water splitting photocatalysts are an energetically demanding and cost-effective method for generating renewable energy. Significant research has been reported to advance this approach. However, the use of organic photocatalysts and the presence of residual catalysts trapped in the porous frameworks present major concerns about the efficiency of this strategy. Herein, we report the photocatalytic evolution of H2 and O2 by a multi-hydroxyl group-decorated metalloporphyrin-based two-dimensional catalyst developed via metal catalyst-free synthetic route. Though metalloporphyrins have long been used for catalytic functions, a heterogeneous photocatalyst delivering both H2 and O2 has not yet been realized. This polymer catalyst design enables the photocatalytic diatomic O2 release, a bottleneck in water splitting, in a facile way. Photocatalytic release of H2 as well as O2 occurs with long-term durability of 20 cycles in 300 days with negligible decrease in efficiency, thus demonstrating the excellent performance of this new catalyst.

Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding